2017
DOI: 10.4236/jwarp.2017.97053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turfgrass Thatch on Water Infiltration, Surface Runoff, and Evaporation

Abstract: The development of a (layer of) thatch in turfgrass causes important changes to near-surface eco-hydrological processes. In this study, we investigated the effects of turfgrass thatch, specifically Kentucky bluegrass (Poa pratensis L.) and red fescue (Festuca rubra L.) on water infiltration, surface runoff, and soil moisture evaporation. The thatches were collected from the field for controlled experiments using packed soil columns under various rainfall conditions. Results indicated that the presence of thatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The PCA results showed that lower soil compaction leads to postponed pond forming on the soil surface layer and the start of the Runoff, which was also observed previously [94][95][96][97]. Moreover, the WSA showed a positive relation with TP and TR because of (1) WSA's capability to create channels within the soil that will enable water to infiltrate and move down the soil profile, which will improve the soil's ability to store more water, thus reducing the water available for runoff [98,99], (2) higher aggregate stability will prevent crusting, since the soil particles are bounded into aggregates that are less prone to soil detachment during the raindrop impact [97,100], and (3) well-aggregated soil had a rougher surface texture due to the presence of clumps and particles, which will enlarge the surface area for rainfall catchment [101].…”
Section: Interrelations Between Propertiessupporting
confidence: 82%
“…The PCA results showed that lower soil compaction leads to postponed pond forming on the soil surface layer and the start of the Runoff, which was also observed previously [94][95][96][97]. Moreover, the WSA showed a positive relation with TP and TR because of (1) WSA's capability to create channels within the soil that will enable water to infiltrate and move down the soil profile, which will improve the soil's ability to store more water, thus reducing the water available for runoff [98,99], (2) higher aggregate stability will prevent crusting, since the soil particles are bounded into aggregates that are less prone to soil detachment during the raindrop impact [97,100], and (3) well-aggregated soil had a rougher surface texture due to the presence of clumps and particles, which will enlarge the surface area for rainfall catchment [101].…”
Section: Interrelations Between Propertiessupporting
confidence: 82%
“…Moreover, there is less published evidence from open-field experiments, and even less pertaining to thatch control-related problems [ 6 , 17 , 18 ]. The objective of the present study aimed at evaluating the efficacy of a commercial product, EM-1, as well as two biostimulant products (ExpA and ExpB), developed by the present research group, on the widely used temperate turf species Agrostis stoloniferous L. Given that field trials provide essential information about biostimulant effects under real-world conditions [ 29 ], the experimentation was conducted under open-field conditions, with the aim of improving the characteristics of the plant rhizosphere, whilst simultaneously ensuring improvements to the plant, an aspect considered necessary in turf management. The present results showed that both ExpA and ExpB, identical in microbial composition, were equally effective in improving certain plant characteristics for quality traits in accordance with the new European regulation (EU) 2019/1009 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the success of AMF’s colonization of creeping bentgrass roots in the present investigation after treatment with ExpB, the benefits of AMF in facilitating the combined beneficial effects of the microbial inoculum and humus in aspects of thatch control may be more evident under water stress conditions. This aspect remains to be investigated and is also warranting of further investigation to substantiate biostimulant claims, for which a minimum of three field trials in the EU are specified under different geoclimatic conditions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated primarily through studies of N saturation in forested ecosystems (Aber et al 1998), higher leaf and litter N content can result in accelerated N cycling processes. In addition, more thatch cover can alter soil moisture content by minimizing evaporative losses and holding more water locally (Liang et al 2017), a particularly important control on tallgrass prairie species (Craine et al 2010). Thatch cover can also limit rates of primary productivity in native tallgrass species by reducing photosynthetically active radiation to growing shoots and preventing cooling of emergent leaves (Knapp and Seastedt 1986).…”
Section: Discussionmentioning
confidence: 99%